Relationships between the duration of mechanical ventilation and its related factors in infants with respiratory distress syndrome in NICU - Sima Sabaghi; Manighe Nourian; Minoo Fallahi; Malihe Nasiri (Tehran University of Medical Sciences, 2016)
Background & Aim: Although mechanical ventilation is a life-saving intervention for many infants with respiratory distress syndrome, it carries potential complications. One of these complications is prolonged duration of mechanical ventilation. More than 15 days of mechanical ventilation is associated with increased risk of cerebral palsy and attention deficit hyperactivity disorder among extremely low birth weight infants. The current study aimed to determine the relationships between the length of mechanical ventilation and its related factors in neonates with respiratory distress syndrome. Methods & Materials: In this analytical study, a convenience sample of 60 premature infants of 33 weeks' gestation or less with respiratory distress syndrome was recruited from three hospitals (Mahdieh, Mofid, and Imam Hossein) affiliated to Shahid Beheshti University of Medical Sciences in 2014-2015. Then, factors related to the length of mechanical ventilation such as sex, type of birth, birth weight, gestational age, Apgar score at the first minute, Apgar score at the fifth minute were assessed. The data were analyzed using descriptive statistics, Pearson correlation, independent t-test, and multiple regression analysis on SPSS software v.20. Results: The mean gestational age was 30.62±1.8 weeks and the mean weight of infants was 1510.33±390.940 grams. The mean length of mechanical ventilation was 3.58±2.97 days. There  were not any correlations between sex, type of birth and the length of mechanical ventilation (P>0.05). Gestational age and weight were significantly correlated to the length of mechanical ventilation (P<0.001). But in adjusted analysis using multiple regression, only gestational age remained a significant factor related to the length of mechanical ventilation (P<0.05). Conclusion: The results of the current study revealed that among the studied factors, only gestational age was a factor affecting the length of mechanical ventilation.